2013
DOI: 10.7860/jcdr/2012/4938.2664
|View full text |Cite
|
Sign up to set email alerts
|

Hysterosalpingographic Tubal Abnormalities in Retroviral (HIV) Positive and Negative Infertile Females

Abstract: Background: HIV and infertility are associated in several ways and the improved treatment options which are available for HIV patients have improved their health, increased their reproductive years and subsequently, their desire to procreate. Objective:The objective was to compare the findings on hysterosalpingography in HIV positive and negative infertile females.Study Design: All the 5250 patients who were referred to the radiodiagnosis unit of the centre in 2011, were counselled about the study, but only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…18 The high rates of HIV are probably because KwaZulu-Natal has the highest HIV burden in SA; the rate amongst antenatal attendees is 37%. 8 It should be noted that 25% of the HIV-infected infertile women in this study had not initiated anti-retroviral (ARV) treatment. Although no side effects or adverse events of HSG were noted in the study for both infected and uninfected women, the study was not designed to evaluate the complications in HIV-infected women following HSG.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…18 The high rates of HIV are probably because KwaZulu-Natal has the highest HIV burden in SA; the rate amongst antenatal attendees is 37%. 8 It should be noted that 25% of the HIV-infected infertile women in this study had not initiated anti-retroviral (ARV) treatment. Although no side effects or adverse events of HSG were noted in the study for both infected and uninfected women, the study was not designed to evaluate the complications in HIV-infected women following HSG.…”
Section: Discussionmentioning
confidence: 92%
“…Yahya et al 7 reported tuboperitoneal factor as the most common cause of infertility (seen in 81% of HIV-infected patients) and the association as statistically significant, with a p-value of 0.048. Similarly, Adegoke et al 8 reported that tubo-peritoneal abnormalities were more common amongst infertile women infected with HIV as compared to those without HIV infection. Adesiyun et al 4 also reported a study on HSG and found that distal tubal occlusion with hydrosalpinx was mainly associated with HIV infection.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Tubal abnormalities can be caused by infections (such as chlamydia, gonorrhea, and tuberculosis) often transmitted sexually, that cause scarring and damage of the tubal tissue, in addition to peritoneal infection, previous surgeries, or endometriosis, and rarely, genetic defects 53 . Subfertility is common in women with HIV, and is usually associated with tubal blockage (most commonly hydrosalpinges) particularly in women with a history of induced abortions and tubal pathologies 54 . Uterine abnormalities can be caused by uterine fibroids, polyps or adenomyosis, or congenital malformations.…”
Section: [H1] Epidemiologymentioning
confidence: 99%